The official SAT study guide - College Entrance Examination Board (New York : College Board, 2019)
"Prepare for the SAT with sample questions, practice tests, and more."--Cover.
Getting ready for the SAT -- Evidence-based reading and writing -- Math -- Eight official practice tests with answer explanations.
"Includes 8 real tests and official answer explanations"--Cover.
"Take the SAT with confidence. The Official SAT Study Guide, from the creators of the SAT, gives you the tools to succeed on test day."--Back cover.
Keywords: SAT (Educational test) -- Study guides; Universities and colleges -- United States -- Entrance examinations -- Study guides; College entrance achievement tests -- Study guides; Study guides